Restoring HOXD10 Exhibits Therapeutic Potential for Ameliorating Malignant Progression and 5-Fluorouracil Resistance in Colorectal Cancer - Pan, Weijie; Wang, Kaijing; Li, Jiayong; Li, Hanhua; Cai, Yuchan; Zhang, Min; Wang, Aili; Wu, Yazhou; Gao, Wei; Weng, Wenhao (Frontiers in Oncology, 2021)
Emerging evidence suggests that hypermethylation of HOXD10 plays an important role in human cancers. However, the biological and clinical impacts of HOXD10 overmethylation and its downstream targets in colorectal cancer remain unknown. We evaluated the methylation level of HOXD10 in paired cancer and normal tissues (n = 42) by using pyrosequencing, followed by validation of the methylation status of HOXD10 from The Cancer Genome Atlas (TCGA) datasets with 302 cancer tissues and 38 normal tissues. The biological function of HOXD10 was characterized in cell lines. We further evaluated the effects of HOXD10 and its targets on chemoresistance in our established resistant cell lines and clinical cohort (n = 66). HOXD10 was found frequently methylated in colorectal cancer, and its hypermethylation correlates with its low expression level, advanced disease, and lymph node metastasis. Functionally, HOXD10 acts as a tumor suppressor gene, in which HOXD10-expressing cells showed suppressed cell proliferation, colony formation ability, and migration and invasion capacity. Mechanistically, DNMT1, DNMT3B, and MeCP2 were recruited in the HOXD10 promoter, and demethylation by 5-Aza-2′-deoxycytidine (5-Aza-CdR) treatment or MeCP2 knockdown can sufficiently induce HOXD10 expression. HOXD10 regulates the expressions of miR-7 and IGFBP3 in a promoter-dependent manner. Restoration of the expression of HOXD10 in 5-fluorouracil (5-FU)-resistant cells significantly upregulates the expressions of miR-7 and IGFBP3 and enhances chemosensitivity to 5-FU. In conclusion, we provide novel evidence that HOXD10 is frequently methylated, silenced, and contributes to the development of colorectal cancers. Restoration of HOXD10 activates the expressions of miR-7 and IGFBP3 and results in an inhibited phenotype biologically, suggesting its potential therapeutic relevance in colorectal cancer (CRC).